Penggunaan Kombinasi Ekstrak Akar Saluang Belum (Lavanga sarmentosa) dengan Akar Kuning (Arcangelisia flava Merr) terhadap Daya Hambat Bakteri Aeromonas hydrophila Secara In Vitro - Maryani Maryani; Kartika Bungas; Hasan Anwar (Universitas Batanghari Jambi, 2020)
Saluang Belum Root (Lavanga sarmentosa) and Yellow Root ((Arcangelisia flava) Merr) plants that have antibacterial effects need to be proven, for this research this program uses Saluang Belum Root (Lavanga sarmentosa) with Yellow Root (Arcangelisia flava) Merr) against bacterial inhibition. Aeromonas hydrophila by In Vitro. The method used in this study was a Completely Randomized Design (CRD) with 6 (six) settings and 3 (three) replications related to the aid of A = 25 gr / 150 ml distilled water, treatment B = 35 gr / 150 ml distilled water, C treatment = 45 gr / 150 ml distilled water, treatment D = 55 gr / 150 ml distilled water, handling E = 500 mg chloromphenicol / 150 ml distilled water, and treatment F = negative control only using the use of 150 ml distilled water. The results of this study indicate a combination of Saluang Belum Root Root (Lavanga sarmentosa) with Yellow Root (Arcangelisia flava Merr) which is able to inhibit the growth of My Aeromonas hydrophila bacteria because it has an antibacterial effect, this can be seen from the results of the zone average (inhibitory power) on each The treatment is the highest clear zone according to the D 55 gr / 150 ml treatment with an average clear zone of 15 mm and the lowest clear zone yield is A 25 gr / 150 ml approval with an average clear zone value of 11 mm. Keywords: Aeromonas hydrophila; Root of Saluang Not yet; Yellow Root; Antibacterial.